Length of Hospice Care among U.S. Adults: 1992-2000 - Beth Han; Robin E. Remsburg; William J. McAuley; Timothy J. Keay; Shirley S. Travis (SAGE Publishing, 2007)
This study examined length of service use among U.S. adult hospice patients based on data from the 1992-2000 National Home and Hospice Care Surveys. With the Kaplan-Meier method, we estimated length of service use of current and discharged hospice patients simultaneously. Using a multivariate Cox proportional hazards model, we examined trends in patients' service use during the 1990s. Findings show that length of service use decreased significantly among adult patients who had Medicare as their only payment source. Although overall length of service use declined significantly in 1996, 1998, and 2000 compared to 1992, it was similar between 1996 and 2000.